2012
DOI: 10.1002/cmdc.201200293
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Analogues with Potent and Selective Anti‐proliferative Activity on Acute Promyelocytic Leukemia: Involvement of Accumulated Misfolded Nuclear Receptor Co‐repressor (N‐CoR) Protein as a Basis for Selective Activity

Abstract: Curcumin arrests the proliferation of acute promyelocytic leukemia (APL) cells by stabilizing the misfolded nuclear receptor co-repressor (N-CoR) protein, thereby sensitizing APL cells to apoptosis induced by the unfolded protein response. This phenomenon was attributed to inhibition of the proteasomal and protease-induced breakdown of misfolded N-CoR by curcumin. Curcumin is, however, a modest inhibitor and affected the viability of APL cells at micromolar concentrations. Modifying curcumin at its conjugated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 53 publications
3
42
0
Order By: Relevance
“…As shown in Figure 2, these groups were present in the earlier hits 32 , 34 , and 39 . 27 Second, asymmetric substitution of the phenyl rings was explored with the above-mentioned groups. Third, the phenyl rings were replaced by pyridines, motivated in part by the good results observed for several cyclohexanones 27 and piperidinones 28 which had similar phenyl-to-pyridine substitution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 2, these groups were present in the earlier hits 32 , 34 , and 39 . 27 Second, asymmetric substitution of the phenyl rings was explored with the above-mentioned groups. Third, the phenyl rings were replaced by pyridines, motivated in part by the good results observed for several cyclohexanones 27 and piperidinones 28 which had similar phenyl-to-pyridine substitution.…”
Section: Resultsmentioning
confidence: 99%
“…Also included in Table 1 are previously determined IC 50 values of selected thiopyranones, cyclohexanones, and piperidinones. 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such studies have shown, e.g., that curcumin induces apoptotic death of human leukemia cells including HL-60 cells and their multidrug-resistant derivatives [8,9,41,42]. We have found that the pro-apoptotic activity of curcumin involves accumulation of ceramide in these cells.…”
Section: Discussionmentioning
confidence: 95%